2013
DOI: 10.1177/1721727x1301100213
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Effect of Esculetin in an Experimental Animal Model of Inflammatory Bowel Disease

Abstract: Esculetin is a coumarin derivative with high antioxidant activity. In a rat experimental model of inflammatory bowel disease induced by trinitrobenzenesulfonic acid, esculetin at the dose of 5mg/Kg displayed intestinal anti-inflammatory activity; however, its mechanism of action needs to be elucidated. Our objective was to evaluate the effects of esculetin on the intestinal inflammatory process and to clarify the mechanism of action of this compound. We also compared its effects with prednisolone and sulphasal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…As pieces of evidence showed, via inducing the expression of antioxidant enzyme HO-1, esculetin significantly inhibited the release of proinflammatory cytokines and mediators, including NO, TNF-α, and MCP-1 (Kim et al, 2014). Moreover, through increasing the defense against ROS, the suppression of the activation and migration of inflammatory cells was found to be helpful for esculetin (Witaicenis et al, 2013). In general, esculetin showed significant potential to be a future therapeutic candidate for the treatment of inflammatory diseases.…”
Section: Antiinflammatory Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…As pieces of evidence showed, via inducing the expression of antioxidant enzyme HO-1, esculetin significantly inhibited the release of proinflammatory cytokines and mediators, including NO, TNF-α, and MCP-1 (Kim et al, 2014). Moreover, through increasing the defense against ROS, the suppression of the activation and migration of inflammatory cells was found to be helpful for esculetin (Witaicenis et al, 2013). In general, esculetin showed significant potential to be a future therapeutic candidate for the treatment of inflammatory diseases.…”
Section: Antiinflammatory Activitymentioning
confidence: 96%
“…The downregulation of the HIF-prolyl hydroxylase (HPH) expression by esculetin (200 μM), leading to the activation of the HIF-1-VEGF pathway that triggers beneficial effects to colitis was suggested by Yum et al (2015). In rats with colitis, it was suggested by Witaicenis et al that esculetin with a dosage of 5 mg/kg not only increases the defense against ROS but also inhibits the secretion of proinflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-lβ, IL-2, and interferon (IFN)-γ, leading to the lower activation and less migration of inflammatory cells (Witaicenis et al, 2013). In mice with fibromyalgia induced by reserpine, esculetin (10 mg/kg) was demonstrated to relieve behavioral and biochemical deficits through the inhibition of the release of proinflammatory cytokines (TNF-α and IL-lβ) as well as the monoamine oxidase-A (MAO-A)mediated depletion of serotonin (Singh et al, 2020).…”
Section: Antiinflammatory Activitymentioning
confidence: 99%
“…Rzodkiewicz et al (2016) showed that 8 could reduce leukotriene B4 level in plasma of rats with adjuvant-induced arthritis, indicating its potential as a drug candidate for the treatment of rheumatoid arthritis. In a rat experimental model of inflammatory bowel disease induced by trinitrobenzenesulfonic acid, coumarin 8 at the dose of 5 mg/Kg exhibited intestinal anti-inflammatory activity (Witaicenis et al 2014).…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…[53]. Esculetin has been shown to obstruct the inflammatory cascade by downregulating the expression of IL-1β, IL-2, IFN-γ, and TNF-α in inflammatory bowel disease [54] and fibromyalgia [55]. Furthermore, esculetin exhibits anti-allergic and anti-inflammatory activity by downregulating the expression of IL-6 and IL-8 in the nasal epithelial cells under in vitro conditions [56].…”
Section: Esculetin In Inflammationmentioning
confidence: 99%